Prevalence of low energy availability in 25 New Zealand elite female rowers - A cross sectional study - Scheffer, J. H.; Dunshea-Mooij, C. A. E.; Armstrong, S.; MacManus, C.; Kilding, A. E. (Journal of Science and Medicine in Sport, 2023)
Objectives To quantify energy availability (EA) in elite female rowers, determine its association with bone mineral density (BMD), and examine the ability of the low energy availability in females-questionnaire (LEAF-Q) and brief eating disorder in athletes-questionnaire (BEDA-Q) to distinguish between low and normal EA.